1992
DOI: 10.1128/jb.174.14.4594-4605.1992
|View full text |Cite
|
Sign up to set email alerts
|

Cloning of the HSP70 gene from Halobacterium marismortui: relatedness of archaebacterial HSP70 to its eubacterial homologs and a model for the evolution of the HSP70 gene

Abstract: Heat shock induces the synthesis of a set of proteins in Halobacterium marismortui whose molecular sizes correspond to the known major heat shock proteins. By using the polymerase chain reaction and degenerate oligonucleotide primers for conserved regions of the 70-kDa heat shock protein (HSP70) family, we All bacterial and eukaryotic species studied to date exhibit increased synthesis of a set of proteins referred to as stress or heat shock proteins (HSPs) in response to a sudden increase in physiological t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
93
1
1

Year Published

1993
1993
2003
2003

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 120 publications
(101 citation statements)
references
References 47 publications
6
93
1
1
Order By: Relevance
“…We have previously shown that the observed polyphyletic branching pattern of archaebacteria is statistically strongly supported by results obtained with different phylogenetic methods (14,15). Furthermore, as discussed in earlier work (12)(13)(14), the possibilities that the observed pattern could be due to the use of paralogous sequences, horizontal gene transfer, or tree reconstruction artifacts are considered highly unlikely. Since a similar branching of archaebacteria with gram-positive species is obtained with a number of other conserved proteins, including glutamate dehydrogenase (1) and glutamine synthetase I (4, 29), we think that these results may not be unusual but may point to a specific relationship between these two groups.…”
Section: Lkyn-rs--k-ikhl--nvvnk-g ---N-p---a-lkhfrsrsscgptr ---Sspa--mentioning
confidence: 48%
See 3 more Smart Citations
“…We have previously shown that the observed polyphyletic branching pattern of archaebacteria is statistically strongly supported by results obtained with different phylogenetic methods (14,15). Furthermore, as discussed in earlier work (12)(13)(14), the possibilities that the observed pattern could be due to the use of paralogous sequences, horizontal gene transfer, or tree reconstruction artifacts are considered highly unlikely. Since a similar branching of archaebacteria with gram-positive species is obtained with a number of other conserved proteins, including glutamate dehydrogenase (1) and glutamine synthetase I (4, 29), we think that these results may not be unusual but may point to a specific relationship between these two groups.…”
Section: Lkyn-rs--k-ikhl--nvvnk-g ---N-p---a-lkhfrsrsscgptr ---Sspa--mentioning
confidence: 48%
“…A multiple alignment of the 2158 ACT ATT TTA G M TCA AAA AAT GAA CAA AAA GAA ACT CAT GGA ATG AGA TAT ATG TTA GAA AAT CCT GAG TTT T h r I l e Leu G l u S e r Lys A s n G l u G l n L y s G l u T h r His G l y M e t A r g T y r M e t Leu G l u A s n P r o G l u P h e 2248 AM M T GCA GTT AAA TTA GTT GAA CAA TTA TCT CCT TTT GAT TGA TTT AAT ATT GCT TAT GAA TCT AAT AAA Lys A s n A L a V a t LYS Leu V a l G L u G l n L e u S e r P r o P h e A s p T r p P h e A s n I l e A l e T y r G l u S e r A s n L y s 2338 ATT AM ATT GGT M T GM ATC GAC CAA ATA AAT GAT GAT ATT TCA ATG ATT GCT ACA GAA TTA AAA ATT GGT I l e Lys I l e G l y A s n G l u I t e A s p G l n I l e A s n Asp A s p I l e S e r M e t I l e A l e T h r G l u Leu Lys I t e G L y 2428 ACT TTA GTA GGT CCA AAA AGA GGT AGA TTA CAA CCA AGT AAA CCA GTT AAT GAA CTT AAT TAT TGA AAT TAT T h r Leu V a l G l y Pro L y s A r g G l y A r g L e u G L n Pro S e r Lys Pro V a l A s n G l u Leu A s n T y r T r p A s n T y r Leu G l y G l y G l y T h r P h e A s p V a l S e r ILe L e u A l a I l e G l y G l y G l y S e r P h e A s p V a l I l e A l a T h r S e r G l y A s n 3785 GGA GAT AAT TTT GAT GAA GAA ATT ATC AAA TGA TTA CTA GGT AAA ATT AAA GCT GAA TAC AAT ATT GAT TTA TCT AAA G l y A s p A s n P h e A s p GLu G l u I l e I l e Lys T r p Leu Leu G l y Lys I l e L y s A l a G l u T y r A s n I l e A s p L e u S e r L y s 3875 TTA CAA AGA TTA AAA GAT GAA GCT GAA AAA GCA AAA ATT AAT TTA TCT AGC CAA TTA GAA GTT GAA ATT AAT TTA CCA L e u G l n A r g Leu Lys A s p G l u A l a G l U L y s A l a L y s I l e A s n L e u S e r S e r G l n L e u G l u V a l G l u I l e A s n L e u P r o 3965 AAT GAA AGT GGA CCA ATT TCT TTT GCA ACT CTA ACA AGA AGT GAA TTT AAC AAA ATT ACA AAA CAT TTA GTT GAC TTG GCT GTG CAA GGT G l n G l u Leu V a l Lys S e r L e u Leu A s n L y s G l u P r o A s n A r g S e r I l e A s n P r o A s p G l u V a l V a l A l e M e t G l y A l a A l a V a l G l n G l y 4235 GGA GTT TTA GCT GGT GAA GTT ACT GAT ATT TTA TTA TTA GAT GTA ACC CCA TTA TCA TTA GGT A T 1 GAA ACA ATG GGT GGA GTT ATG ACA G l y V a l Leu A l a G l y G l u V a l T h r A s p I l e Leu L e u L e u A s p V a l T h r P r o L e u S e r L e u G l y I l e G l u T h r M e t G l y G l y V a l M e t T h r 46 to 47% over the entire length of the protein. A number of Hsp70 family protein sequence signatures that are characteristic of the major groups of species have been identified previously (13)(14)(15)(16). One prominent sequence signature is a large insert of 23 to 27 amino acids that is present in the N-terminal quadrant of all gram-negative bacteria and eukaryotic Hsp70, but absent in the homologs from archaebacteria and grampositive bacteria.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Such a comparison evaluating the distribution of this epitope among DnaK proteins might shed light on the relatedness of members of the purple bacterial group. Comparison of DnaK sequences has also been suggested as a taxonomic tool for evaluation of distantly related organisms (14).…”
Section: Discussionmentioning
confidence: 99%